Die wisselwerking tussen profeet en gehoor in die boek Esegiël - H. F. van Rooy (In die Skriflig, 1994)
The interaction between prophet and audience is one of the important elements of the prophetic process. This interaction is closely related to the audience's acceptance or rejection of the prophetic message. The reaction of the prophet could either be to adapt his message to the expectations of the audience or to affirm his message. This paper explores this interaction in the Book of Ezekiel. The interaction is clear in the quotation of popular proverbs and the words of the exiles, the people in Jerusalem and the enemies of the people, in symbolic actions that evoked questions from the prophet's audience and in the interpretation of certain oracles against the background of certain expectations of the prophet's audience. In some instances the interaction may be purely rhetorical, but in other instances it reflects events in the time of the prophet.